PREPARATION OF AMITRIPTYLINE HYDROCHLORIDE FILMS USING EUDRAGIT RL 100 AND HYDROXY PROPYL METHYL CELLULOSE POLYMERS AND THEIR IN-VITRO EVALUATION FOR EFFECTIVE TRANSDERMAL DELIVERY: Pharmaceutical Science-Pharmaceutics - R.VIJAYA; S.SURESHKUMAR; M.PRAKASH; S.UMAMAHESWARI; T. SENBAGAPRIYA; A.UMAMAHESWARI (International Journal of Life Science and Pharma Research, 2012)
Objective: The aim of the present study was to prepare a transdermal film for the antidepressant Amitriptyline hydrochloride to improve the treatment efficacy. Method: The matrix type transdermal film was prepared by solvent evaporation method using two different polymers Eudragit RL 100 & hydroxy propyl methyl cellulose (HPMC) in different ratios using solvents ethyl alcohol and dichloromethane. Dibutyl phthalate was used as a plasticizer. The films were evaluated for physical properties such as thickness, percentage moisture absorption, percentage moisture loss, drug content, folding endurance and flatness. The in-vitro release studies were performed using USP dissolution apparatus. The optimized film was further evaluated for skin permeation, stability and skin irritation studies. Results: The data obtained shows that the transdermal film F4 (Eudragit RL 100 & HPMC at ratio of 2:1) had produced a highest drug release of 98 ±1.03% up to 24 hrs. When the release study was conducted for F4 on an animal skin there was a drastic decrease (61.56 ± 0.14%) in the percentage of drug release. The kinetics of drug release followed higuchi model with diffusion controlled mechanism. Skin irritation studies showed no sign of edema and erythema. There was no interaction found between the drug and polymer as proved by FTIR studies. The film F4 was found to be stable with respect to drug content. Conclusion: The prepared film of Amitriptyline HCl is found to provide a controlled release and permeation which is suitable for transdermal delivery